CLASSIFICATION OF CRIMINAL PROCEDURAL LEGAL RELATIONS IN THE CONDITIONS OF MODERN CRIMINAL JUDICIARY - Вінниченко, В. (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2020)
The article considers the classification of criminal procedural legal relations in the conditionsof modern criminal procedural legislation of Ukraine. Scientific approaches to the classification ofcriminal procedural legal relations, subjects of criminal procedural legal relations and their legal per-sonality are studied.The purpose of the article is to carry out the scientific classification of criminal procedural legalrelations in the conditions of the new criminal procedural legislation.The author investigated: scientific approaches to the classification of criminal procedural legalrelations; the concept of the subject of criminal procedural law and the relationship with the subject ofcriminal procedural legal relations; The legal personality of the subject of criminal procedural law andits elements, such as legal capacity, legal capacity, tort. During the research, a critical analysis of thisscientific material was made and our own scientific approaches to the legal capacity, capacity, tortof the subjects of criminal procedural legal relations were developed. During the author’s research anumber of methods of scientific cognition were applied, in particular, as: method of scientific formal-ization; axiomatic method; hypothetical-deductive method.Approaches to the classification of criminal legal relations are considered and the analysis of thementioned approaches to the classification of subjects of criminal procedural legal relations is given.The analysis of the criminal procedural legislation and sources of the international public law iscarried out.Theoretical approaches are generalized by the method of scientific deduction and the classifi-cation of criminal procedural legal relations is carried out, which can be applied in the conditions ofmodern criminal proceedings.The author’s substantiated classification of criminal procedural legal relations, which is based onthe subjects of criminal procedural legal relations, is given

В статті розглянуто класифікацію кримінальних процесуальних правовідносин в умовах сучасного кримінального процесуального законодавства України. Досліджено наукові підходи до класифікації кримінальних процесуальних правовідносин, суб’єкти кримінальних процесуальних правовідносин та їх правосуб’єктність. Метою статті є здійснення наукової класифікації кримінальних процесуальних правовідносин в умовах дії нового кримінального процесуального законодавства. Автором досліджено наукові підходи щодо класифікації кримінальних процесуальних правовідносин; поняття суб’єкта кримінального процесуального права та співвідношення з суб’єктом кримінальних процесуальних правовідносин; правосуб’єктність суб’єкта кримінального процесуального права та її елементи, як дієздатність, правоздатність, деліктоздатність. Зроблено критичний аналіз зазначеного наукового матеріалу та вироблено власні наукові підходи до правоздатності, дієздатності, деліктоздатності суб’єктів кримінальних процесуальних правовідносин. Під час авторського дослідження застосовано низку методів наукового пізнання, зокрема метод наукової формалізації, аксіоматичний метод, гіпотико-дедуктивний метод. Розглянуто підходи до класифікації кримінальних правовідносин та надано аналіз зазначених підходів до класифікації суб’єктів кримінальних процесуальних правовідносин. Проведено аналіз кримінального процесуального законодавства та джерел міжнародного публічного права. Узагальнено методом наукової дедукції теоретичні підходи та проведено класифікацію кримінальних процесуальних правовідносин, що може буті застосовано в умовах сучасного кримінального судочинства. Наведено авторську обґрунтовану класифікацію кримінальних процесуальних правовідносин, яка базується на суб’єктах кримінальних процесуальних правовідносин.
Класифікація кримінальних процесуальних правовідносин в умовах сучасного кримінального судочинства
Keywords: classification of criminal procedural legal relations; criminal proceedings; subject of criminal proceedings; subject of criminal procedural legal relations; signs of criminal procedural legal relations; criminal procedural capacity; criminal procedural capacityprotection of human rights; state security; fight against crime; law enforcement agencies; класифікація кримінальних процесуальних правовідносин; кримінальний процес; суб’єкт кримінального процесу; суб’єкт кримінальних процесуальних правовідносин; ознаки кримінальних процесуальних правовідносин; кримінальна процесуальна дієздатність; кримінальна процесуальна правоздатність; захист прав людини; державна безпека; боротьба зі злочинністю; органи правопорядку